Evaluation of laboratory findings indicating pancreatitis in healthy lean, obese, and diabetic cats - Freja K. Jørgensen; Charlotte R. Bjornvad; Birgit Krabbe; Stinna Nybroe; Ida N. Kieler (Journal of Veterinary Internal Medicine)
Abstract Background Obesity is a risk factor for diabetes mellitus, which commonly coexists with pancreatitis in cats. However, obesity has not previously been associated with pancreatitis in cats. Objectives To evaluate factors affecting serum concentrations of pancreatic lipase immunoreactivity (fPLI), trypsin‐like immunoreactivity (fTLI), cobalamin and folate in clinically healthy lean, overweight and obese, or diabetic cats. Animals Seventy‐nine client‐owned cats (27 healthy lean [LN, BCS 4‐5/9], 30 healthy overweight and obese [OW, BCS 7‐9/9], and 22 diabetic [DM]) were included. Methods Cross‐sectional study. The cats underwent physical examination, and blood tests. Linear regression models compared differences in fPLI, fTLI, cobalamin, and folate concentrations. Fisher's exact test assessed the proportions of cats with fPLI and fTLI indicative of pancreatitis, and hypocobalaminemia. A random forest algorithm identified explanatory variables for cats having fPLI levels indicative of pancreatitis. Results No LN cats, while 6/30 (20%) of OW and 10/22 (45%) of DM cats had fPLI concentrations indicative of pancreatitis. Body condition score (P = .02) and body weight (P = .002) were positively associated with fPLI levels in LN and OW cats. Higher fPLI, and lower cobalamin concentrations were associated with higher age across groups. Conclusions and Clinical Importance Body condition score and body weight were associated with higher fPLI levels in nondiabetic cats. A larger proportion of OW and DM cats had fPLI concentrations indicative of pancreatitis compared to LN cats. Whether this indicates subclinical pancreatitis remains to be determined. Hypocobalaminemia was less frequent in OW compared to DM cats.